Predictors for MTB Culture-Positivity among HIV-Infected Smear-Negative Presumptive Tuberculosis Patients in Uganda: Application of New Tuberculosis Diagnostic Technology - Nakiyingi, Lydia; Nonyane, Bareng A. S.; Ssengooba, Willy; Kirenga, Bruce J.; Nakanjako, Damalie; Lubega, Gloria; Byakika-Kibwika, Pauline; Joloba, Moses L.; Ellner, Jerry J.; Dorman, Susan E.; Mayanja-Kizza, Harriet; Manabe, Yukari C. (PLoS ONE, 2015)
The existing World Health Organization diagnostic algorithms for smear-negative TB perform poorly in HIV-infected individuals. New TB diagnostics such as urine TB lipoarabinomannan (LAM) could improve the accuracy and reduce delays in TB diagnosis in HIVinfected smear-negative presumptive TB. We sought to determine predictors for MTB culture- positivity among these patients.
Keywords: MTB Culture-Positivity; HIV-Infected; Tuberculosis Patients; Uganda; Tuberculosis Diagnostic Technology